Sustainable Drainage System Analysis In The Institut Teknologi Sumatera (ITERA) - daus, firdaus (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2023)
The Institut Teknologi Sumatera is a new university that still requires planning and infrastructure development, one of the development needed is the construction of a drainage system, namely a sustainable drainage system that adheres to the concept of water conservation. The purpose of this research is to analyze topographic conditions, as well as the performance of the existing drainage system in ITERA and to develop recommendations for a sustainable drainage system. In this study, several stages were carried out, first analyzing the topographical conditions in ITERA. The second is to analyze the existing drainage capacity, which is to compare the existing drainage capacity to the runoff that occurs when it rains. The calculation of runoff discharge is obtained from hydrological analysis of rainfall data using the annual maximum partial series method. Third, synthesizing the connectivity between drainage segments to the reservoirs in ITERA. The results of several analyzes above show that, firstly, the topography in ITERA is relatively flat with the most dominant elevations being 85 - 100 m and 100 - 105 m. Second, the calculation results show that the existing drainage capacity is still able to accommodate the runoff that occurs. So for now it is still safe against inundation and flooding. Third, the results show that there are several existing drainages that have not been connected to other drainage segments and water does not run off to the designated place as a reservoir, namely the reservoir.